(untitled) (Bangladesh Journal of Zoology, 2015)
Diversity of aquatic insects in relation to the physicochemical parameters of the river Buriganga and Shitalakhya were studied from January to December 2013. A total of 9,891 individuals of aquatic insects representing 22 families under 6 orders were collected and identified. Higher number of insects were recorded from the river Shitalakhya (5,493) than the river Buriganga (4,398). Representatives of the family Culicidae were found to be dominant in the river Buriganga (23.28%) than Shitalakhya (20.70%). Specimens under the order Ephemeroptera and Trichoptera were found only in the river Shitalakhya. The highest diversity of Shannon Weiner Index (2.98), Evenness (0.98) and Taxa Richness (0.98) were recorded in the river Shitalakhya than the river Buriganga. This indicated the less pollution and presence of higher diversity of aquatic insects in the Shitalakhya river. The highest temperature, pH, EC, TDS, COD was observed in Buriganga in dry season and highest DO was observed in Shitalakhya in monsoon. From the present investigation it may be concluded here that the river Buriganga was more polluted than the river Shitalakhya. Bangladesh J. Zool. 43(1): 63-72, 2015